Polylactic acid composite material, preparation method thereof and polylactic acid product

By setting a multi-layer structure of polylactic acid composite material on the surface of polylactic acid particles, the problem of insufficient mechanical properties of polylactic acid materials is solved, the tensile strength and elongation of break are significantly improved, and the interface between inorganic materials and polylactic acid is improved. Compatibility improves overall mechanical properties.

CN119192802APending Publication Date: 2024-12-27BEIJING GRAPHENE TECH RES INST CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411179843.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The mechanical properties of polylactic acid materials are insufficient, especially in terms of tensile strength and elongation at break, and the interface compatibility with inorganic materials is poor, resulting in uneven performance and insufficient binding force.

Method used

The first organic layer and the first inorganic layer are sequentially set on the surface of the polylactic acid particles, and the second organic layer is set on the surface of the first inorganic layer, controlling the melting point of each layer is lower than the melting point of the polylactic acid particles to ensure the first organic layer The mass ratio to polylactic acid particles is within the range of 0.1~5:100, and inorganic materials such as carbon nanomaterials and nanosilicon dioxide are used to improve material performance.

Benefits of technology

It effectively improves the tensile strength and elongation of breaking polylactic acid composite materials, improves the interface compatibility between inorganic materials and polylactic acid, and enhances the overall mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192802A_ABST
    Figure CN119192802A_ABST
Patent Text Reader

Abstract

The invention relates to a polylactic acid composite material, a preparation method thereof and a polylactic acid product. The polylactic acid composite material comprises polylactic acid particles, a first organic layer, a first inorganic layer and a second organic layer, the first organic layer, the first inorganic layer and the second organic layer are sequentially arranged on the surfaces of the polylactic acid particles, the melting points of the first organic layer and the second organic layer are lower than the melting point of the polylactic acid particles, and the mass ratio of the first organic layer to the polylactic acid particles is (0.1-5): 100. The polylactic acid composite material is relatively high in tensile strength and elongation at break.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of material technology, and in particular to a polylactic acid composite material and a preparation method thereof, and a polylactic acid product. Background Art

[0002] Polylactic acid (PLA) is a biodegradable material with broad market prospects and is considered to be an environmentally friendly material that can replace traditional plastics. However, its performance has certain limitations in some aspects, such as insufficient mechanical properties.

[0003] Therefore, it is necessary to provide a polylactic acid material with higher mechanical properties. Summary of the invention

[0004] Based on this, the present application provides a polylactic acid composite material with high mechanical properties, a preparation method thereof, and a polylactic acid product.

[0005] The technical solution of this application to solve the above technical problems is as follows.

[0006] In a first aspect, the present application provides a polylactic acid composite material, comprising polylactic acid particles, a first organic layer, a first inorganic layer, and a second organic layer sequentially arranged on the surface of the polylactic acid particles, wherein the melting points of the first organic layer and the second organic layer are lower than the melting point of the polylactic acid particles, and the mass ratio of the first organic layer to the polylactic acid particles is (0.1~5):100.

[0007] In some embodiments, in the polylactic acid composite material, the melting points of the first organic layer and the second organic layer are independently no higher than 100°C.

[0008] In some of the embodiments, in the polylactic acid composite material, the first organic layer and the second organic layer independently include at least one of citrate esters, acylated glycerol fatty acid esters, isosorbide esters, palmitic acid, polyethylene glycol, hyperbranched polyester and polybutylene succinate.

[0009] In some of the embodiments, in the polylactic acid composite material, the mass ratio of the second organic layer to the polylactic acid particles is (0.1-5):100.

[0010] In some embodiments, in the polylactic acid composite material, the first inorganic layer satisfies one of the following characteristics:

[0011] (1) The first inorganic layer includes at least one of carbon nanomaterials, nano-silicon dioxide materials and tourmaline nanopowders;

[0012] (2) The first inorganic layer includes at least one of graphene, graphene oxide and fumed nano-silicon dioxide;

[0013] (3) The mass ratio of the first inorganic layer to the polylactic acid particles is (0.01-5):100.

[0014] In some of the embodiments, in the polylactic acid composite material, the particle size of the polylactic acid particles is 1 mm to 10 mm.

[0015] In some of the embodiments, in the polylactic acid composite material, the surface of the second organic layer further includes a second inorganic layer and a third organic layer which are alternately arranged in sequence.

[0016] The second aspect of the present application provides a method for preparing a polylactic acid composite material, comprising the following steps:

[0017] preparing a first organic layer on the surface of the polylactic acid particles;

[0018] preparing a first inorganic layer on the surface of the first organic layer;

[0019] preparing a second organic layer on the surface of the first inorganic layer;

[0020] The melting points of the first organic layer and the second organic layer are lower than the melting point of the polylactic acid particles, and the mass ratio of the first organic layer to the polylactic acid particles is (0.1~5):100.

[0021] In some embodiments, the method for preparing the polylactic acid composite material comprises the following steps:

[0022] Mixing polylactic acid particles and a first organic material and performing a first stirring to prepare a first organic layer on the surface of the polylactic acid particles to obtain a first intermediate;

[0023] The first intermediate and the first inorganic material are mixed and stirred for a second time to prepare a first inorganic layer on the surface of the first organic layer to obtain a second intermediate;

[0024] The second intermediate and the second organic material are mixed and subjected to a third stirring to prepare a second organic layer on the surface of the first inorganic layer;

[0025] The temperature of the first stirring is not lower than the melting point of the first organic material, the temperature of the third stirring is not lower than the melting point of the second organic material, and the temperatures of the first stirring, the second stirring and the third stirring are lower than the melting point of the polylactic acid particles.

[0026] In some embodiments, in the method for preparing the polylactic acid composite material, the temperatures of the first stirring and the third stirring are independently 50° C. to 150° C.

[0027] The third aspect of the present application provides a polylactic acid product, comprising the polylactic acid composite material and / or the polylactic acid composite material prepared by the above preparation method.

[0028] Compared with the prior art, the polylactic acid composite material of the present application has the following beneficial effects:

[0029] The polylactic acid composite material of the present application is characterized in that a first organic layer, a first inorganic layer, and a second organic layer are sequentially arranged on the surface of polylactic acid particles, and the melting points of the first organic layer and the second organic layer are controlled to be lower than the melting point of the polylactic acid particles, and the mass ratio of the first organic layer to the polylactic acid particles is controlled. On the basis of ensuring the elongation at break, the tensile strength of the polylactic acid composite material can be effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0031] Figure 1 A schematic diagram of the structure of a polylactic acid composite material provided in one embodiment;

[0032] Figure 2 A schematic diagram of the cross-sectional structure of a polylactic acid composite material provided in another embodiment.

[0033] Reference numerals:

[0034] 10: polylactic acid composite material; 11: polylactic acid particles; 12: first organic layer; 13: first inorganic layer; 14: second organic layer; 15: second inorganic layer; 16: third organic layer. DETAILED DESCRIPTION

[0035] References to embodiments of the present invention will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present invention. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present invention without departing from the scope or spirit of the present invention. For example, a feature illustrated or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0036] Therefore, it is intended that the present invention covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present invention are disclosed in or are obvious from the following detailed description. Those of ordinary skill in the art will appreciate that this discussion is only a description of exemplary embodiments and is not intended to limit the broader aspects of the present invention.

[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0038] The term "comprises", "comprising" or any other variant thereof is intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of more restrictions, the elements defined by the sentence "comprising one..." do not exclude the presence of other identical elements in the process, method, article or equipment including the elements. The indefinite articles "a kind of" and "an" before the elements or components of the present invention are not restrictive to the quantity requirements (i.e., the number of occurrences) of the elements or components. Therefore, "a" or "a kind of" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the number clearly refers only to the singular form. The meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0039] The weight of the relevant components mentioned in the description of the embodiments of the present invention may not only refer to the specific content of each component, but also indicate the weight ratio between the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the description of the embodiments of the present invention, it is within the scope disclosed in the description of the embodiments of the present invention. Specifically, the weight described in the description of the embodiments of the present invention may be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0040] Except as shown in the operating examples or otherwise indicated, all numbers used in the specification and claims to indicate the amount of ingredients, physicochemical properties, etc. are understood to be adjusted by the term "about" in all cases. For example, therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.1, 1.3, 1.5, 2, 2.75, 3, 3.80, 4 and 5, etc.

[0041] Studies have found that using plasticizers to modify polylactic acid can improve the plasticity of polylactic acid to a certain extent, but at the same time it will reduce the mechanical strength of polylactic acid.

[0042] Mixing polylactic acid with inorganic materials will have the following disadvantages:

[0043] (1) Uneven dispersion:

[0044] The poor uniformity of inorganic materials in the PLA matrix leads to large local performance differences. For example, some areas may have increased brittleness due to the aggregation of inorganic materials, while other areas may not achieve the expected performance improvement due to too little inorganic material content.

[0045] (2) Interface compatibility issues:

[0046] The interfacial compatibility between polylactic acid and inorganic materials is often poor, which may weaken the bonding between the two, thereby affecting the overall mechanical properties of the composite material and making it prone to cracking or delamination at the interface.

[0047] See also Figure 1 In one embodiment of the present application, a polylactic acid composite material 10 is provided, comprising polylactic acid particles 11, a first organic layer 12, a first inorganic layer 13 and a second organic layer 14 sequentially arranged on the surface of the polylactic acid particles, the melting points of the first organic layer 12 and the second organic layer 14 are lower than the melting points of the polylactic acid particles 11, and the mass ratio of the first organic layer 12 to the polylactic acid particles 11 is (0.1~5):100.

[0048] The polylactic acid composite material of the present application is characterized in that a first organic layer, a first inorganic layer, and a second organic layer are sequentially arranged on the surface of polylactic acid particles, and the melting points of the first organic layer and the second organic layer are controlled to be lower than the melting point of the polylactic acid particles, and the mass ratio of the first organic layer to the polylactic acid particles is controlled. On the basis of ensuring the elongation at break, the tensile strength of the polylactic acid composite material can be effectively improved.

[0049] By controlling the melting point of the first organic layer to be lower than the melting point of the polylactic acid particles and controlling the mass ratio of the first organic layer to the polylactic acid particles, the first organic layer is evenly arranged on the surface of the polylactic acid particles and has better bonding strength; by arranging the first organic layer between the polylactic acid particles and the first inorganic layer, the problem of poor interface compatibility between the inorganic material and the polylactic acid can be solved, thereby improving the bonding strength between the first inorganic layer and the substrate; continuing to arrange the second organic layer on the surface of the first inorganic layer can further prevent the first inorganic layer from cracking or stratification.

[0050] It can be further understood that the mass ratio of the first organic layer to the polylactic acid particles includes but is not limited to 0.1:100, 0.2:100, 0.3:100, 0.4:100, 0.5:100, 0.6:100, 0.7:100, 0.8:100, 1:100, 1.5:100, 2:100, 2.5:100, 3:100, 3.5:100, 4:100, 4.5:100, and 5:100; in some examples, the mass ratio of any two of these point values ​​can be within the range formed by the end values, the same below.

[0051] Optionally, the mass ratio of the first organic layer to the polylactic acid particles is (0.1~1):100.

[0052] Furthermore, the mass ratio of the first organic layer to the polylactic acid particles is (0.5~1):100.

[0053] It can be understood that the first organic layer is disposed on the surface of the polylactic acid particles, the first inorganic layer is disposed on the surface of the first organic layer, and the second organic layer is disposed on the surface of the first inorganic layer.

[0054] In some of the examples, in the polylactic acid composite material, the first organic layer covers the surface of the polylactic acid particles, the first inorganic layer covers the surface of the first organic layer, and the second organic layer covers the surface of the first inorganic layer.

[0055] In some of the examples, in the polylactic acid composite material, the melting points of the first organic layer and the second organic layer are independently no higher than 100°C.

[0056] It can be understood that the melting point of the first organic layer and the melting point of the second organic layer refer to the melting points of the first organic material in the first organic layer and the second organic material in the second organic layer, respectively; further, the melting points of the first organic layer and the second organic layer may be the same or different; the first organic material and the second organic material may be the same or different; further, the melting points of the first organic layer and the second organic layer independently include but are not limited to 0°C, 10°C, 20°C, 50°C, 60°C, 70°C, 80°C, 90°C, and 100°C.

[0057] In some of the examples, in the polylactic acid composite material, the melting points of the first organic layer and the second organic layer are independently no higher than 80°C.

[0058] In some of the examples, in the polylactic acid composite material, the first organic layer and the second organic layer independently include at least one of citrate esters, acylated glycerol fatty acid esters, isosorbide esters, palmitic acid, polyethylene glycol, hyperbranched polyester and polybutylene succinate.

[0059] In some examples, the acylated glycerol fatty acid esters include, but are not limited to, ACETEM1290.

[0060] In some examples, the isosorbide esters include, but are not limited to, ISD-1436.

[0061] In some examples, the hyperbranched polyester includes, but is not limited to, CYD-T151.

[0062] In some of the examples, in the polylactic acid composite material, the mass ratio of the second organic layer to the polylactic acid particles is (0.1~5):100.

[0063] It can be understood that the mass ratio of the second organic layer to the polylactic acid particles includes but is not limited to 0.1:100, 0.2:100, 0.3:100, 0.4:100, 0.5:100, 0.6:100, 0.7:100, 0.8:100, 1:100, 1.5:100, 2:100, 2.5:100, 3:100, 3.5:100, 4:100, 4.5:100, and 5:100; in some examples, ... any two of these point values ​​can be used as end values ​​within the range, the same below.

[0064] Optionally, the mass ratio of the second organic layer to the polylactic acid particles is (0.1~1):100.

[0065] Furthermore, the mass ratio of the second organic layer to the polylactic acid particles is (0.5~1):100.

[0066] In some of the examples, in the polylactic acid composite material, the first inorganic layer includes at least one of carbon nanomaterials, nano-silicon dioxide materials, and tourmaline nanopowders.

[0067] In some of the examples, in the polylactic acid composite material, the first inorganic layer includes at least one of graphene, graphene oxide, and fumed nano-silica.

[0068] In some of the examples, in the polylactic acid composite material, the mass ratio of the first inorganic layer to the polylactic acid particles is (0.01~5):100.

[0069] It can be understood that the mass ratio of the first inorganic layer to the polylactic acid particles includes but is not limited to 0.01:100, 0.05:100, 0.1:100, 0.2:100, 0.3:100, 0.4:100, 0.5:100, 0.6:100, 0.7:100, 0.8:100, 1:100, 1.5:100, 2:100, 2.5:100, 3:100, 3.5:100, 4:100, 4.5:100, and 5:100; in some examples, ... any two of these point values ​​can be within the range formed by the end values, the same below.

[0070] Optionally, the mass ratio of the first inorganic layer to the polylactic acid particles is (0.01-2):100.

[0071] Furthermore, the mass ratio of the first inorganic layer to the polylactic acid particles is (0.1~1):100.

[0072] In some of the examples, in the polylactic acid composite materials, the particle size of the polylactic acid particles is 1 mm to 10 mm.

[0073] It will be appreciated that the particle size of the polylactic acid particles includes, but is not limited to, 1 mm, 2 mm, 3 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, and 10 mm.

[0074] In some of the examples, in the polylactic acid composite material, the surface of the second organic layer further includes a second inorganic layer and a third organic layer which are alternately arranged in sequence.

[0075] See also Figure 2 In some examples, a polylactic acid composite material 10a is provided, including polylactic acid particles 11, a first organic layer 12, a first inorganic layer 13, a second organic layer 14, a second inorganic layer 15 and a third organic layer 16 sequentially arranged on the surface of the polylactic acid particles.

[0076] It can be understood that the second inorganic layer is arranged on the surface of the second organic layer, and the third organic layer is arranged on the surface of the second inorganic layer; it can be further understood that the second inorganic layer and the third organic layer are not limited to one layer, and can also be multiple layers, that is, the second inorganic layer a, the third organic layer a, the second inorganic layer b, the third organic layer b, the second inorganic layer c, the third organic layer and so on are alternately arranged on the surface of the second organic layer.

[0077] An embodiment of the present application provides a method for preparing a polylactic acid composite material, comprising the following steps:

[0078] preparing a first organic layer on the surface of the polylactic acid particles;

[0079] preparing a first inorganic layer on the surface of the first organic layer;

[0080] preparing a second organic layer on the surface of the first inorganic layer;

[0081] The melting points of the first organic layer and the second organic layer are lower than the melting point of the polylactic acid particles, and the mass ratio of the first organic layer to the polylactic acid particles is (0.1-5):100.

[0082] It can be understood that the preparation method of the polylactic acid composite material provided in the present application can prepare the above-mentioned polylactic acid composite material, and the above-mentioned polylactic acid composite material can be prepared by the preparation method of the polylactic acid composite material provided in the present application, but is not limited to this preparation method; further, the preparation method of the polylactic acid composite material provided in the present application and the characteristics of the above-mentioned polylactic acid composite material can be mutually applicable.

[0083] In some of the examples, the method for preparing the polylactic acid composite material includes the following steps:

[0084] S100: mixing polylactic acid particles and a first organic material and performing a first stirring to prepare a first organic layer on the surface of the polylactic acid particles to obtain a first intermediate;

[0085] S200: mixing the first intermediate and the first inorganic material and performing a second stirring to prepare a first inorganic layer on the surface of the first organic layer to obtain a second intermediate;

[0086] S300: mixing the second intermediate and the second organic material and performing a third stirring to prepare a second organic layer on the surface of the first inorganic layer;

[0087] The temperature of the first stirring is not lower than the melting point of the first organic material, the temperature of the third stirring is not lower than the melting point of the second organic material, and the temperatures of the first stirring, the second stirring and the third stirring are lower than the melting point of the polylactic acid particles.

[0088] By controlling the melting points of the first organic layer and the second organic layer to be lower than the melting point of the polylactic acid particles, that is, controlling the melting points of the first organic material and the second organic material to be lower than the melting point of the polylactic acid particles, controlling the temperature of the first stirring to be not lower than the melting point of the first organic material, the temperature of the third stirring to be not lower than the melting point of the second organic material, and the temperatures of the first stirring, the second stirring and the third stirring to be lower than the melting point of the polylactic acid particles, and controlling the mass ratio of the first organic layer to the polylactic acid particles, it can be ensured that the polylactic acid particles do not undergo morphological changes, and the first organic material is melted and evenly loaded on the surface of the polylactic acid particles, and the second organic material is evenly loaded on the surface of the first inorganic layer, which can effectively improve the tensile strength and elongation at break of the polylactic acid composite material.

[0089] In some of the examples, in the method for preparing the polylactic acid composite material, the temperatures of the first stirring and the third stirring are independently 50° C. to 150° C.

[0090] In some of the examples, in the method for preparing the polylactic acid composite material, the temperature of the second stirring is 50° C. to 150° C.

[0091] It can be understood that the temperatures of the first stirring, the second stirring and the third stirring may be the same or different; further, the temperatures of the first stirring, the second stirring and the third stirring may independently include but are not limited to 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, and 150°C.

[0092] It can be understood that the temperatures of the first stirring, the second stirring and the third stirring can heat the polylactic acid in advance, and there is no need to heat them separately later, which saves energy.

[0093] That is, in some of the examples, the method for preparing the polylactic acid composite material includes the following steps:

[0094] The polylactic acid is heated, and then the heated polylactic acid particles and the first organic material are mixed and stirred, and then the first inorganic material is added and mixed and stirred, and then the second organic material is added and mixed and stirred.

[0095] Furthermore, the heating temperature is higher than the melting point of the first organic material and the second organic material. Furthermore, the heating temperature is 2° C. to 10° C. higher than the melting point of the first organic material and the second organic material.

[0096] In some of the examples, in the method for preparing the polylactic acid composite material, the rotation speeds of the first stirring and the third stirring are independently 100 rpm to 300 rpm.

[0097] It can be understood that the rotation speeds of the first stirring and the third stirring include but are not limited to 100 rpm, 120 rpm, 150 rpm, 180 rpm, 200 rpm, 220 rpm, 250 rpm, 280 rpm, and 300 rpm respectively and independently.

[0098] In some of the examples, in the method for preparing the polylactic acid composite material, the rotation speed of the second stirring is 20 rpm~100 rpm.

[0099] It can be understood that the rotation speed of the second stirring includes but is not limited to 20 rpm, 30 rpm, 40 rpm, 50 rpm, 60 rpm, 70 rpm, 80 rpm, 90 rpm, and 100 rpm.

[0100] In some of the examples, in the preparation method of the polylactic acid composite material, after the third stirring step is completed, the method further includes a fourth stirring step of the material obtained in the third stirring step, and the rotation speed of the fourth stirring is not lower than the rotation speed of the third stirring.

[0101] In some of the examples, in the method for preparing the polylactic acid composite material, the rotation speed of the fourth stirring is 300 rpm~800 rpm.

[0102] It can be understood that the rotation speed of the fourth stirring includes but is not limited to 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, and 800 rpm.

[0103] After the raw materials of each layer are added and coated on the surface, stirring is continued at a relatively high speed to ensure that each layer is fully infiltrated and evenly dispersed.

[0104] In some of the examples, the method for preparing the polylactic acid composite material may further include the steps of sequentially preparing a second inorganic layer and a third inorganic layer on the surface of the second organic layer before the fourth stirring step and after the third stirring step.

[0105] The rotation speed when setting the third organic layer is 100 rpm~300 rpm, and the rotation speed when setting the second inorganic layer is 20 rpm~100 rpm.

[0106] One embodiment of the present application provides the use of the above-mentioned polylactic acid composite material and / or the polylactic acid composite material prepared by the above-mentioned preparation method in the preparation of polylactic acid products.

[0107] Another embodiment of the present application provides a polylactic acid product, including the polylactic acid composite material and / or the polylactic acid composite material prepared by the above preparation method.

[0108] The polylactic acid product of the present application includes the above-mentioned polylactic acid composite material provided in the present application and / or the polylactic acid composite material prepared by the above-mentioned preparation method, and thus has at least the same advantages as the above-mentioned polylactic acid composite material and / or the polylactic acid composite material prepared by the above-mentioned preparation method.

[0109] In some of the embodiments, the polylactic acid products include but are not limited to food packaging, agricultural mulch, surgical sutures, tissue engineering scaffolds, drug release systems, automotive interior parts, electronic products, tableware, cups, straws, furniture, etc.

[0110] In some embodiments, the material of the polylactic acid product may be the polylactic acid composite material and / or the polylactic acid composite material obtained by the above-mentioned preparation method, that is, the polylactic acid product is directly prepared by using the polylactic acid composite material and / or the polylactic acid composite material obtained by the above-mentioned preparation method. In other embodiments, the material of the polylactic acid product may include other materials in addition to the polylactic acid composite material and / or the polylactic acid composite material obtained by the above-mentioned preparation method.

[0111] The present application is further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present application are not limited thereto.

[0112] Example 1

[0113] (1) Weigh 10 kg of polylactic acid particles (particle size of 3 mm to 5 mm), heat them to 100°C in an oven, add them to a high-speed mixer, add 30 g of polyethylene glycol with a melting point of about 50°C, and stir at 100 rpm for 10 min to coat the surface of the polylactic acid particles to form a polyethylene glycol coating layer;

[0114] (2) Add 30 g of graphene to the high-speed mixer and stir at 30 rpm for 10 min to coat the surface of the polyethylene glycol coating layer, thereby forming a graphene coating layer on the surface of the polyethylene glycol coating layer;

[0115] (3) Add 30 g of polyethylene glycol and stir at 100 rpm for 10 min to coat the graphene coating layer; continue stirring at 500 rpm for 60 min to obtain a polylactic acid composite material. The melt index after blending and granulation is 85 cm 3 / 10min (210℃, 2.16 Kg).

[0116] Example 2

[0117] (1) Weigh 10 kg of polylactic acid particles, stir them in a high-speed mixer at 500 rpm for 1 hour to raise the temperature to 100°C, add 10 g of palmitic acid with a melting point of about 64°C, and stir at 100 rpm for 10 min to coat the surface of the polylactic acid particles to form a palmitic acid coating layer;

[0118] (2) Add 10 g of graphene oxide to a high-speed mixer and stir at 30 rpm for 10 min to coat the surface of the palmitic acid coating layer, thereby forming a graphene oxide layer on the surface of the palmitic acid coating layer;

[0119] (3) Add 10 g palmitic acid and stir at 100 rpm for 10 min to coat the surface of the graphene oxide coating layer; continue stirring at 500 rpm for 60 min to obtain a polylactic acid composite material. The melt index after blending and granulation is 88 cm 3 / 10min (210℃, 2.16 Kg).

[0120] Example 3

[0121] (1) Weigh 10 kg of polylactic acid particles, heat them to 120°C in an oven, add them to a high-speed mixer, add 100 g of polyethylene glycol, and stir at 100 rpm for 10 min to coat the surface of the polylactic acid particles to form a polyethylene glycol coating layer;

[0122] (2) adding 100 g of graphene oxide and stirring at 30 rpm for 10 min to coat the surface of the polyethylene glycol coating layer, thereby forming a graphene oxide coating layer on the surface of the polyethylene glycol coating layer;

[0123] (3) adding 50 g of hyperbranched polyester CYD-T151 having a melting point of about 50°C, and stirring at 100 rpm for 10 min to coat the surface of the graphene oxide coating layer, thereby forming a CYD-T151 coating layer on the surface of the graphene oxide coating layer;

[0124] (4) Add 100 g of fumed nano-silica and stir at 30 rpm for 10 min to coat the surface of the CYD-T151 coating layer to form a fumed nano-silica coating layer;

[0125] (5) Add 50 g of liquid isosorbide ester ISD-1436 and stir at 100 rpm for 10 min to coat the surface of the gas-phase nano-silica coating layer; continue stirring at 500 rpm for 30 min to obtain a polylactic acid composite material. The melt index after blending and granulation is 496 cm 3 / 10min (210℃, 2.16 Kg).

[0126] The melt-blown cloth was prepared by mixing 10 PHr with melt-blown polylactic acid material, with a filtration efficiency of 90%, a resistance of 20Pa, a longitudinal tensile strength of 30N, and a breaking productivity of more than 20%.

[0127] Example 4

[0128] (1) Weigh 10 kg of polylactic acid particles, heat them to 80°C in an oven, add them to a high-speed mixer, add 10 g of polyethylene glycol, and stir at 100 rpm for 10 min to coat the surface of the polylactic acid particles to form a polyethylene glycol coating layer;

[0129] (2) adding 10 g of graphene oxide and stirring at 30 rpm for 10 min to coat the surface of the polyethylene glycol coating layer, thereby forming a graphene oxide coating layer on the surface of the polyethylene glycol coating layer;

[0130] (3) Add 10 g of liquid isosorbide ester ISD-1436, stir at 100 rpm for 10 min to coat the surface of the graphene oxide coating layer, and form an ISD-1436 coating layer on the surface of the graphene oxide coating layer to obtain a polylactic acid composite material. The melt index after blending and granulation is 92 cm 3 / 10min (210℃, 2.16 Kg).

[0131] Example 5

[0132] (1) Weigh 10 kg of polylactic acid powder, stir it in a high-speed mixer at 500 rpm for 1 hour to raise the temperature to 80°C, add 100 g of liquid isosorbide ester ISD-1436, and stir it at 300 rpm for 10 min to coat the surface of the polylactic acid particles to form an ISD-1436 coating layer;

[0133] (2) Add 100 g of graphene oxide and stir at 100 rpm for 20 min to coat the surface of the ISD-1436 coating layer to form a graphene oxide layer;

[0134] (3) Add 50 g of liquid isosorbide ester ISD-1436 and stir at 100 rpm for 10 min to coat the surface of the graphene oxide coating layer; continue stirring at 500 rpm for 60 min to obtain a polylactic acid composite material. The melt index after blending and granulation is 263 cm 3 / 10min (210℃, 2.16 Kg).

[0135] Example 6

[0136] The method is basically the same as Example 1, except that, in Example 6, the polyethylene glycol in step (1) and step (3) of Example 1 is replaced with palmitic acid of equal mass, and finally a polylactic acid composite material is obtained. The melt index after blending and granulation is 170 cm 3 / 10min (210℃, 2.16 Kg).

[0137] Example 7

[0138] The method is basically the same as Example 1, except that in Example 7, the polyethylene glycol in step (3) of Example 1 is replaced with an equal mass of palmitic acid. Finally, a polylactic acid composite material is obtained, and the melt index after blending and granulation is 160 cm 3 / 10min (210℃, 2.16 Kg).

[0139] Example 8

[0140] The method is basically the same as Example 1, except that the amount of polyethylene glycol added in step (1) of Example 8 is 200 g, and the amount of polyethylene glycol added in step (3) is 100 g. The polylactic acid composite material is finally obtained, and the melt index after blending and granulation is 550 cm 3 / 10min (210℃, 2.16 Kg).

[0141] Example 9

[0142] The method is basically the same as Example 1, except that the amount of polyethylene glycol added in step (1) of Example 9 is 400 g, and the amount of polyethylene glycol added in step (3) is 100 g. The polylactic acid composite material is finally obtained, and the melt index after blending and granulation is 630 cm 3 / 10min (210℃, 2.16 Kg).

[0143] Example 10

[0144] (1) Weigh 10 kg of polylactic acid particles and heat them to 50°C. Add them into a high-speed mixer and stir them at 500 rpm for 100 min until the temperature reaches 100°C. Add 400 g of acylated glycerol fatty acid ester plasticizer ACETEM1290 and stir them at 200 rpm for 10 min to coat the surface of the polylactic acid particles.

[0145] (2) Add 500 g of graphene and stir at 30 rpm for 10 min to coat it;

[0146] (3) Add 100 g of liquid isosorbide ester ISD-1436, stir at 200 rpm for 10 min to coat the graphene coating layer, and continue stirring at 500 rpm for 60 min to obtain a polylactic acid composite material. The melt index after blending and granulation is 510 cm 3 / 10min (210℃, 2.16 Kg).

[0147] Comparative Example 1

[0148] 10 kg of polylactic acid particles were weighed and heated to 100 °C, added to a high-speed mixer, and 30 g of graphene oxide and 60 g of polyethylene glycol with a melting point of about 50 °C were added at the same time. The mixture was stirred at 500 rpm for 120 min and allowed to stand for 10 min to obtain a polylactic acid composite material. The melt index after blending and granulation was 74 cm 3 / 10min (210℃, 2.16 Kg).

[0149] Comparative Example 2

[0150] 10 kg of polylactic acid particles were weighed, 150 g of liquid isosorbide ISD-1436 and 100 g of graphene were added, and the mixture was stirred at 500 rpm for 60 min to mix them. The mixture was allowed to stand for 10 min to obtain a polylactic acid composite material. The melt index after blending and granulation was 80 cm 3 / 10min (210℃, 2.16 Kg).

[0151] Comparative Example 3

[0152] Weigh 10 kg of polylactic acid particles, add them to a high-speed mixer, add 10 g of graphene, stir at 500 rpm for 120 min to mix and heat to 110°C, let stand for 30 min, add 20 g of polyethylene glycol, stir at 100 rpm for 10 min to coat, let stand for 10 min to obtain a polylactic acid composite material, that is, in the final polylactic acid composite material, the surface of the polylactic acid particles is an inorganic layer and an organic layer in sequence. The melt index after blending and granulation is 78 cm 3 / 10min (210℃, 2.16 Kg).

[0153] Comparative Example 4

[0154] The method is basically the same as Example 1, except that the amount of polyethylene glycol added in step (1) of Comparative Example 4 is 1 kg, and the polylactic acid composite material is finally obtained. The melt index after blending and granulation is 780 cm 3 / 10min (210℃, 2.16 Kg).

[0155] Comparative Example 5

[0156] The method is basically the same as Example 1, except that, in Comparative Example 5, the polyethylene glycol in step (1) and step (3) of Example 1 is replaced by an equal mass of hyperbranched polyester CYD-817 having a melting point of about 180°C, and a polylactic acid composite material is finally obtained. The melt index after blending and granulation is 170 cm 3 / 10min (210℃, 2.16 Kg).

[0157] The polylactic acid composite materials prepared in each embodiment and comparative example were coated by a solution method, and the tensile strength and elongation at break were tested with reference to GBT1040.1 and GBT1040.3. The results are shown in Table 1.

[0158] Table 1

[0159]

[0160] It can be seen from Table 1 that, compared with the comparative example, the tensile strength and elongation at break of the polylactic acid composite materials prepared in each embodiment are higher.

[0161] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0162] The above-described embodiments only express several implementation methods of the present application, which is convenient for understanding the technical solution of the present application in detail, but it cannot be understood as limiting the scope of protection of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several modifications and improvements can be made, which all belong to the scope of protection of the present application. It should be understood that the technical solutions obtained by those skilled in the art through logical analysis, reasoning or limited experiments on the basis of the technical solutions provided in the present application are all within the scope of protection of the claims attached to the present application. Therefore, the scope of protection of the patent of this application shall be based on the contents of the attached claims, and the description and drawings can be used to explain the contents of the claims.

Claims

1. A polylactic acid composite material, characterized in that: The invention comprises polylactic acid particles, a first organic layer, a first inorganic layer and a second organic layer sequentially arranged on the surface of the polylactic acid particles, the melting points of the first organic layer and the second organic layer are lower than the melting point of the polylactic acid particles, and the mass ratio of the first organic layer to the polylactic acid particles is (0.1~5):

100.

2. The polylactic acid composite material according to claim 1, characterized in that: The melting points of the first organic layer and the second organic layer are independently no higher than 100°C.

3. The polylactic acid composite material according to claim 1, characterized in that: The first organic layer and the second organic layer independently include at least one of citrate esters, acylated glycerol fatty acid esters, isosorbide esters, palmitic acid, polyethylene glycol, hyperbranched polyester and polybutylene succinate.

4. The polylactic acid composite material according to claim 1, characterized in that: The mass ratio of the second organic layer to the polylactic acid particles is (0.1-5):

100.

5. The polylactic acid composite material according to any one of claims 1 to 4, characterized in that: The first inorganic layer satisfies one of the following characteristics: (1) The first inorganic layer includes at least one of carbon nanomaterials, nano-silicon dioxide materials and tourmaline nanopowders; (2) The first inorganic layer includes at least one of graphene, graphene oxide and fumed nano-silicon dioxide; (3) The mass ratio of the first inorganic layer to the polylactic acid particles is (0.01-5):

100.

6. The polylactic acid composite material according to any one of claims 1 to 4, characterized in that: The particle size of the polylactic acid particles is 1 mm to 10 mm.

7. The polylactic acid composite material according to any one of claims 1 to 4, characterized in that: The surface of the second organic layer also includes a second inorganic layer and a third organic layer which are alternately arranged in sequence.

8. A method for preparing a polylactic acid composite material, characterized in that: The following steps are involved: preparing a first organic layer on the surface of the polylactic acid particles; preparing a first inorganic layer on the surface of the first organic layer; preparing a second organic layer on the surface of the first inorganic layer; The melting points of the first organic layer and the second organic layer are lower than the melting point of the polylactic acid particles, and the mass ratio of the first organic layer to the polylactic acid particles is (0.1~5):

100.

9. The preparation method according to claim 8, characterized in that: The following steps are involved: Mixing polylactic acid particles and a first organic material and performing a first stirring to prepare a first organic layer on the surface of the polylactic acid particles to obtain a first intermediate; The first intermediate and the first inorganic material are mixed and stirred for a second time to prepare a first inorganic layer on the surface of the first organic layer to obtain a second intermediate; The second intermediate and the second organic material are mixed and subjected to a third stirring to prepare a second organic layer on the surface of the first inorganic layer; The temperature of the first stirring is not lower than the melting point of the first organic material, the temperature of the third stirring is not lower than the melting point of the second organic material, and the temperatures of the first stirring, the second stirring and the third stirring are lower than the melting point of the polylactic acid particles.

10. The preparation method according to claim 9, characterized in that: The temperatures of the first stirring and the third stirring are independently 50° C. to 150° C.

11. A polylactic acid product, characterized in that: The invention comprises the polylactic acid composite material as described in any one of claims 1 to 7 and / or the polylactic acid composite material prepared by the preparation method as described in any one of claims 8 to 10.